Foundations of information and knowledge systems : 9th International Symposium, FoIKS 2016, Linz, Austria, March 7-11, 2016. Proceedings /: 9th International Symposium, FoIKS 2016, Linz, Austria, March 7-11, 2016. Proceedings. (2016) - Unknown
No abstract available